Complement components as promoters of immunological tolerance in dendritic cells. (January 2019) - Luque, Ana; Serrano, Inmaculada; Aran, Josep M.
Abstract: Complement and dendritic cells (DCs) share many functional features that drive the outcome of immune-inflammatory processes. Both have a sentinel function, acting as danger sensors specialized for a rapid, comprehensive and selective action against potential threats without damaging the healthy host cells. But while complement has been considered as a "master alarm" system poised for direct pathogen killing, DCs are regarded as "master regulators" or orchestrators of a vast range of effector immune cells for an effective immune response against threatening insults. The original definition of the complement system, coined to denote its auxiliary function to enhance or assist in the role of antibodies or phagocytes to clear microbes or damaged cells, envisaged an important crosstalk between the complement and the mononuclear phagocyte systems. More recent studies have shown that, depending on the microenvironmental conditions, several complement effectors are competent to influence the differentiation and/or function of different DC subsets toward immunogenicity or tolerance. In this review we will infer about the capability of complement activators and inhibitors to "condition" a tolerogenic and anti-inflammatory immune response by direct interaction with DC surface receptors, and about the implications of this knowledge to devise new complement-based therapeutic approaches for autoimmune pathologies.